Dyadic association between aggressive pretend play and children's anger expression. (5th October 2020) - Rao, Zhen; Fink, Elian; Gibson, Jenny
Abstract : This study investigates the association between children's peer‐reported expression of anger and their pretend play with aggressive/negative themes observed during spontaneous play with classmates. Participants comprised 104 Chinese children ( Mage = 8.98 years, SD = 0.97, 49% girls) and were filmed playing in peer dyads with toys. Aggressive and non‐aggressive negative pretend themes were coded at five‐second intervals for 10 minutes. Children's expression of anger in real situations was reported by peers. Analysis using actor–partner interdependence modelling (APIM) revealed significant partner effects, indicating that children were more likely to engage in pretend play with aggressive themes when they were playing with a partner who was perceived by their peers as more easily angered. It was also found that boys were more likely to engage in pretend play with both aggressive and non‐aggressive negative themes compared with girls.